Sistem Pembelajaran Berbasis Weblog pada Mahasiswa MPI STAI Sangatta Kutai Timur - Miftakhul Rizal M. (Mudir : Jurnal Manajemen Pendidikan, 2020)
The aim of the instruction is attained competences a subject by the learner. Simplely, the instruction has a system, they are begun from material understanding, task and evaluation. The character of the computer subject is practice. Thus, the learner must be able to implement the theory to the practical using computer. There were the learners has no a practicing tool. Then, sometimes there were the learners can’t attend in the class. In order to the learning process must be proceed, either the learner who has no notebook or attended in the class, then implemented the weblog based learning. They can access the materials on the weblog by everywhere, anytime and anywhere. They can upload the tasks too. Therefore, the learning process has stayed proceed by the learner who cant attend in the class. The purpose of this research is describing implement the system of the weblog based learning toward the learner of the Islamic Education Management department STAI Sangatta Kutai Timur. This research is descriptive qualitative research. The system of the instruction is a study process of the learner that be begun from understanding materials, do the tasks and evaluation. The system of the weblog based learning is informing the material by internet technology and the web as displaying information. Thus, the weblog can access by anywere, anytime and everywhere. The results of this research is implementing weblog based learning that be begun from preparing materials by lectures, then creating weblog, uploading materials by lectures, doing the tasks by learners and then the system of the learning process be evaluated by lectures. The learner can use and understand the instruction on the weblog easily. The learning process has stayed proceed either the learner whose cant attend in the class or has no leptop that be used in the class. The effectiveness of the learning system is good to be implemented in the learning process. Based on the results of the research, the conclusion of this research is the system of the weblog based learning toward the learner of Islamic Education Management department STAI Sangatta Kutai timur has 5 steps, they are (1) the lectures prepare the materials, (2) the lectures create the weblog, (3) the lectures upload the materials on the weblog, (4) the learners do and upload the tasks, (5) the lectures evaluate the learing system that has been implemented.